Análise dos impactos do novo modelo de competitividade do sistema financeiro nacional no desempenho dos empregados dos Bancos Públicos de Varejo: o caso do BRC S/A - Fraga, Marcelo Loyola (2002)
The study it has as mam focus present a reference to analyze the individual behavior of the bank' s retail employees in the presence of the necessity of adequacy to the used strategy to face the current competitive market. It shows the importance of the analysis of symbolic dimension for the organizations, to the businesses and the relations between the actors in the enterprise contexto It demonstrates the recent main changes in the National FinanciaI system, that have taken the inserted organizations to search adaptations forms and between them review its processes of management and programs of training and development of people. It traces the current profile of the Bank BRC SI A, making a historical briefmg and approaching the human resources, computerization, the financiaI sanitation project and the operational performance of the last years. It concludes that the cultural features of the Bank BRC SI A in its majority reduce its capacity to adjust the performance form of the private banks. Exist few cultural traces that favor the bank adaptability, which we can indicate the commitment, the devotion and the loyalty ofthe bank staff(that already had been bigger in the past). Other factors also contribute to make it difficult its adaptability, such as paternalism, the formalism, impunity, the spectator position among others features, these are common in the Brazilian companies, as we will see in the frrst chapter. Regard to this, it will be necessary a strong persistence and desire to breach the inertia ofthe organization, as a constancy of intentions, so that the transformations happen and the bank reach the adaptation to the market. In the case, this must be the task of the leadership: to be persistent, perspicacious and flexible the sufficient to maintain the process and lead it to the efficient formo Still, it was contacted that exist resistance and difficulties to make possible the necessary transformations to the bank acts as a private bank. Some resistances are common and others are specific and pro per of each observed situation.